Produced water treatment using two-phase partitioning bioreactor. Issue 48 (20th October 2016) - Piemonte, V.; Prisciandaro, M.; Cassese, A.; Di Paola, L.; Barba, D.
Abstract: Produced waters (PW) are the largest waste associated to the production of oil and gas; they contain dissolved salts, oil (dissolved and scattered organic compounds), chemicals and salt intolerant additives to the oil well operations, suspended particles, sand and other compounds, making their treatment very tricky. In this paper, we propose the use of a two-phase partitioning bioreactor (TPPB) for the biological treatment of PWs. We model the application the TPPB on the stream after classical pre-treatment stages: the reactor functioning is based on the controlled release of substrate by means of a solvent. This study aims at developing a mathematical model for a TPPB adopting oleic alcohol (Adol 85 NF) as a solvent; we test its reliability by means of a sensitivity analysis, so to evaluate its efficiency for COD removal in a PW stream, aimed at water reuse.